Analisis Motivasi Belajar Dan Student Engagement Di Pendidikan Tinggi - Christine Adriani Karambut; Jacob Tateol Silangen Makapedua; Daisy Iriany Erny Sundah; Grace Joice Silvana Neltje Rumimper (Universitas Merdeka Madiun, 2025)
Student engagement and learning motivation are important factors in higher education that influence academic success and overall learning outcomes. The purpose of this study was to analyze student learning motivation and student engagement. The sample of this study was students majoring in Business Administration at the Manado State Polytechnic totaling 100 respondents. The sampling technique in this study was convenience sampling, by sending a questionnaire link to students via a WhatsApp group. Data analysis was carried out by describing the data in the form of percentages and average values with the aim of providing a contextual picture of the reality at the research location. The results of the analysis explained that the average value of student learning motivation was included in the moderate category and student engagement was included in the good category. However, there are several items that need to be improved, including finding that there are still not enough students who try to study harder to make up for their previous low scores if their exam scores are still low or in other words they do not try to achieve better scores. Meanwhile, for student engagement, it was found that only a small number of students are actively involved in extracurricular activities on campus. Because extracurricular activities on campus are less interesting.